Improving reading skills by using Tyler model with the help of Quizizz - Husna, Wafa Nurul; Sauri, Sofyan; Al Farisi, Mohamad Zaka (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
Based on the results of the documentary research, the average score of the fifth-graders at Madrasah Diniyah Al-Fadlilah on Arabic subject is still low (below the Minimum Criteria of Mastery Learning). The purpose of this research is to determine the impact of the implementation of MTBMQ (Tyler-Model-Based Quizziz Learning Media) or Tyler model along with Quizizz on students' reading skills in Arabic subject, as well as to find the issues and solutions in the implementation of MTBMQ. This research utilizes a one group pre-test post-test design. The data are collected through multiple choice tests, along with semi-open Likert Scale questionnaires. Due to the fact that the research data are normally distributed, the researchers decide to use parametric statistical tests. The results show that this implementation has a significant effect on the students' reading skills in Arabic subject. Furthermore, the test results of the paired sample t-test show a sig (2-tailed) value of 0.000 less than 0.025. It means that after implementing MTBMQ, students' score has increased. The result of the N-Gain test, namely 0.65, also shows that MTBMQ is efficient to be implemented to improve students’ reading skills, especially when the material is in the moderate category. The results of the Likert Scale questionnaire show that the main hindrances in implementing the MTBMQ are that students experience problems when logging into the Quizizz web and submitting answers, having difficulty finding the meaning of a word in the dictionary, and a lack of interest in learning to read.